Response of Pakcoy (Brassica rapa L.) Growth and Yield to the Application of Goat Urine and Mutiara NPK Fertilizer - Sherina Br Bangun; Agus Susanto Ginting; Wajib Pandia (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
The rapid harvest cycle of pakcoy and its high nutritional value have increased its cultivation intensity in Indonesia, followed by rising production needs. This experiment evaluated the response of pakcoy (Brassica rapa L.) growth and yield to the combined application of goat urine liquid organic fertilizer and NPK Mutiara fertilizer. The study was carried out in Kutagaluh Village, Tiganderket District, Karo Regency, North Sumatra. A factorial randomized block design with three replications was applied. Goat urine fertilizer treatments consisted of U0 (0 ml/L), U1 (75 ml/L), U2 (150 ml/L), and U3 (225 ml/L), while NPK Mutiara fertilizer treatments included N0 (0 g), N1 (5 g), N2 (10 g), and N3 (15 g). Observations indicated that both single and combined treatments significantly improved the growth and production performance of pakcoy.